2019
DOI: 10.1002/cam4.2675
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CERS6‐AS1 functions as a malignancy promoter in breast cancer by binding to IGF2BP3 to enhance the stability of CERS6 mRNA

Abstract: Breast cancer (BC) leads to the highest mortality in women worldwide, characterized by inevitable proliferation and metastasis of BC cells. Mounting evidence confirm that lncRNAs play a significant role in the tumorigenesis and development of BC. lncRNA CERS6‐AS1 is a novel discovery, and its role and molecular mechanism in BC has not been studied. In this study, it was discovered that CERS6‐AS1 was overexpressed in BC tissues and cells. CERS6‐AS1 accelerated cell proliferation and suppressed cell apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“… 32 Bao et al indicated that CERS6-AS1 enhances the stability of CERS6 mRNA and acts as an oncogene in breast cancer through binding to IGF2BP3. 33 Based on previous studies, we speculated that DARS-AS1 may mediate the progression of cervical cancer via interacting with IGF2BP3 to regulate the expressions of oncogenes (for example, c-Myc gene). However, the detailed mechanisms whereby DARS-AS1/IGF2BP3 regulated the growth and invasion of cervical cancer cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Bao et al indicated that CERS6-AS1 enhances the stability of CERS6 mRNA and acts as an oncogene in breast cancer through binding to IGF2BP3. 33 Based on previous studies, we speculated that DARS-AS1 may mediate the progression of cervical cancer via interacting with IGF2BP3 to regulate the expressions of oncogenes (for example, c-Myc gene). However, the detailed mechanisms whereby DARS-AS1/IGF2BP3 regulated the growth and invasion of cervical cancer cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…28 Long noncoding RNA CERS6-AS1 in combination with IGF2BP3 can improve the stability of CERS6 mRNA that plays roles in breast cancer. 29 In another study, IGF2BP3 was differentially expressed among three ocular cancers. 30 In CRC, increased IGF2BP3 expression has been shown to promote the invasive pattern of CRC in vitro and vivo .…”
Section: Discussionmentioning
confidence: 94%
“…m6A readers are a group of proteins that recognize m6A-modified RNAs and then regulate multiple processes involving RNA, such as RNA stability, translation, splicing and transport. IGF2BP2 and IGF2BP3 play important roles in mRNA stability [ 29 , 30 ]. It has been identified that IGF2BPs recruit target transcripts to cytoplasmic protein-RNA complexes (mRNPs).…”
Section: Discussionmentioning
confidence: 99%